PENGARUH EDUKASI KESEHATAN VIDEO STOP MOTION TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG PMS (Jurnal Kesehatan Siliwangi, 2021)
Background: Health problems in adolescents are having extramarital sex, using NAPZA and sexually transmitted diseases such as Gonorrhea and Chlamydia by 37% and Syphilis by 44% and its spread occurs in the adolescent age group. Adolescent HIV/AIDS cases were 50,282 cases in 2019.The cause of the high rate of sexually transmitted diseases is the lack of education and knowledge for adolescents. Reproductive health knowledge is important for adolescents as a preventive effort from an early age. Objective: to know the impact of health education through stop motion video on young women’s knowledge and attitudes about sexually transmitted diseases at SMPN 11 Sampit. Method: pre experimental designs with one group pretest- posttest. Population and Sample: population of 83 young women in grades 7 and 8 with a sample of 46 young women. Using non parametric test and Wilcoxon test. Result: obtained Asymp.Sig result. (2-tailed) 0.005 on knowledge and 0.000 on attitude < 0.05, meaning stop motion video affects young women's knowledge and attitudes. Conclusion: there was the impact of stop motion video on young women's knowledge and attitudes about sexually transmitted diseases. Suggestions: This stop motion video can be used to provide information and increase the knowledge and attitude of young women of SMPN 11 Sampit about sexually transmitted diseases.